Consequences of Family Financial Burden for the Children with Autism Spectrum Disorder - Bhuiyan, Mahbubur Rahman; Islam, Md Ziaul (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder that causes problems with thinking, reasoning, language, and interacting with others. Around one out of 160 children in the world suffer from autism spectrum disorder (ASD). Objective: To investigate the consequence of the financial burden faced by families on children with ASD. Methods: A cross-sectional study of 154 children with ASD was conducted from July 2015 to June 2016, using a systematic sampling technique, and data was collected using face-to-face interview method through semi-structured questionnaires. Results: The monthly family income and overall treatment cost was Tk. 41785.71±23936.45 and Tk. 23076.62±15341.09 correspondingly. Consequences included impairment of professional life of parents (97.4%), mental stress (98.1%) and financial constraints (89.6%). About 52.2% families had financial restraints due to financial burden which were notably higher when compared with others (p<0.05). Additionally, medical expenses were higher in families with higher family income (r=0.526, p<0.005). Conclusion: ASD is a complex problem that has significant financial impacts on victims' families and results in a variety of consequences for families, including poor work, stress, relationships with relatives, and financial constraints. ASD is a public health problem in Bangladesh and early diagnosis is essential to understand the actual burden in the country. JAFMC Bangladesh, Vol 21, No 1 (June) 2025:02-06